2020
DOI: 10.1002/aelm.202000485
|View full text |Cite
|
Sign up to set email alerts
|

Moving Ions Vary Electronic Conductivity in Lead Bromide Perovskite Single Crystals through Dynamic Doping

Abstract: encountered in solar cell engineering. One of them is caused by the presence of mobile ions and how these species alter the internal electrical field, interact with the contact materials, or modulate electronic properties. [3-6] Upon biasing, charged moving ions accumulate in the vicinity of the outer interfaces causing electrical field partial shielding. [7-9] It has also been reported how intrinsic defects chemically react with the electrodes giving rise to losses in performance and device instabilities. [10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 53 publications
6
56
0
Order By: Relevance
“…The connection of ion distribution and electronic doping density has been recently corroborated using long-time impedance relaxation. 164 Zero-bias HF resistive features slowly recover steady-state values after poling, indicating that the overall ion concentration establishes the effective electronic conductivity through a dynamic doping mechanism. That approach allows for an indirect determination of the ionic diffusion coefficient, which also results in the range of 10 −8 cm 2 s −1 .…”
Section: Ionic Diffusion and Transmission Line Observationmentioning
confidence: 99%
“…The connection of ion distribution and electronic doping density has been recently corroborated using long-time impedance relaxation. 164 Zero-bias HF resistive features slowly recover steady-state values after poling, indicating that the overall ion concentration establishes the effective electronic conductivity through a dynamic doping mechanism. That approach allows for an indirect determination of the ionic diffusion coefficient, which also results in the range of 10 −8 cm 2 s −1 .…”
Section: Ionic Diffusion and Transmission Line Observationmentioning
confidence: 99%
“…The high-frequency resistance ( R ) values were normalized and shown to follow a trend R ∝ t 1/2 (see Figure S6 ), in agreement with the IDD model (see section S2 of the Supporting Information). 17 , 21 …”
Section: Measurement Of Current Transientsmentioning
confidence: 99%
“… Time of flight (right-hand color bar) as a function of mobility and effective charge carrier density for the BVM regime of SCLC as in eq 1 . Parameters as for MAPbBr3 single crystal: V = 100 V, L = 2 mm, ϵ r = 76, 21 V 0 = 10 V. Note that the charge carrier density axis may refer to either ionic or electronic charge carriers in each case. …”
Section: Analysis Of Ionic Transit Timementioning
confidence: 99%
“…The linear fitting of C vs ε 0 A / L gives the dielectric constant. García-Batlle et al used IS on polished MAPbBr 3 SCs with chromium electrodes coated on the opposite faces and performed the measurements inside a metallic box that acted as a Faraday cage, under dark conditions . It was shown that moving ions cause dynamic doping, which affects the electronic conductivity in the MAPbBr 3 SCs, as these moving ions act as mobile dopants and locally vary the carrier density (Figure a).…”
Section: Impedance Spectroscopy For Mhpscsmentioning
confidence: 99%
“…(a) Variation of the impedance (i) as a function of the increasing bias with total measuring time ∼20 min at each voltage and (ii) after removing 5 V bias and evolution with time, and (iii) a detailed view of the variation of the impedance after removing 5 V bias and evolution with time for smaller impedances (last 5 h of the experiment). Reproduced with permission from ref . Distributed under a Creative Commons Attribution Non Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0).…”
Section: Impedance Spectroscopy For Mhpscsmentioning
confidence: 99%